Enhancing Language Acquisition With AI - Tirkashev Dilshodjon Sharobiddin Ugli (Researchparks Publishing, 2023)
Language acquisition is a complex process that requires extensive practice, exposure, and personalized feedback. AI-powered technologies have revolutionized language learning by providing learners with tools and resources that enhance their language acquisition journey. In this section, we will explore various ways in which AI is enhancing language acquisition.